Aplikasi Arang Kompos Bioaktif Berbasis Limbah Kelapa dan Lama Inkubasi untuk Meningkatkan Pertumbuhan Tanaman Kedelai pada Tanah Ultisol - Rini Suryani; Setiawan Setiawan; Ismail Astar (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2025)
The use of Ultisol soil for agriculture has problems, namely low soil organic matter and acidity. This can be overcome by adding organic matter to the soil to act as an ameliorant. The ameliorant can be applied by utilizing coconut waste that has been processed into bioactive compost charcoal. Bioactive compost charcoal is a mixture of charcoal (biochar) and compost composted using Trichoderma harzianum. This study aims to determine the effect of bioactive compost charcoal and incubation period on soybean growth in Ultisol soil. This study used a completely randomized design (CRD) factorial pattern, consisting of two treatment factors. The first factor was bioactive compost charcoal with 4 levels (0; 5; 10; 15 tons ha⁻¹) and the second factor was incubation period with 3 levels (0; 2; 4 weeks). Each treatment was repeated 3 times, consisting of 3 plants, for a total of 108 plants. The results of this study showed that a dose of 15 tons ha⁻¹ of bioactive compost charcoal significantly increased plant height (46,05 cm), number of leaves (55,19 leaves), root volume (7,44 cm³), and plant dry weight (14,40 g), while a dose of 10 tons ha⁻¹ resulted in the highest number of soybean branches (5,37 branches) in Ultisol soil.